MODERN APPROACHES TO THE DEVELOPMENT OF THE TEACHER’S ABILITY - Djumaeva Sanobar Absaatovna, Makhmudova Gulnoza Yuldoshevna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
The article presents the features of the implementation of axiological, cultural, activity, acmeological and competence approaches, in their organic unity, in the process of professional training of a teacher.